Variação na produção e qualidade do leite de vacas da raça Holandesa em função da estação do ano e ordem de parto - Souza, Rodrigo de (2008)
unction of the calving season. Lactation order and calving season cause variation in the milk production, being important the use of strategies to minimize the heat stress mainly in the lactation pick. Larger careful should be taken with cows starting from 4th lactation, because these present a higher SSC and the heat stress can favor the mastitis occurrence